Sensibilisation à l’environnement d’un collège alsacien et d’une école malgache - David Di Paolo (Revue de Primatologie)
Since 2010, the Mulhouse zoo organizes school pedagogical projects on Madagascar ecology subjects. It has developed tools allowing classrooms to awake their ecological awareness and to establish a correspondence with Malagasy children. We present in this paper the example of a Mulhouse secondary school which has been involved in this program for 5 years. Each year, the Mulhouse zoo carries out a pedagogical work that takes place both in classrooms (biology, geography and art lessons) as well as in the zoo. Three annual visits to the zoo allow to children (1) to enhance their understanding of the fauna and flora, this aspect being completed by a personal bibliography produced by children; (2) to introduce notions on the phenotypic classification of primates by observing animals and the help of simple arrays of determining criteria ; (3) to improve their ecological awareness with tangible and common examples like the deforestation in Madagascar or the invasive species introduction, pupils are invited to think about these subjects and to suggest theoretical solutions ; (4) to observe the interspecific behavioral differences and the sexual hierarchy of lemurs using simple ethological observations ("all occurrences sampling" methods) of several species.